Isocyanide-Based MCRs: Straightforward Access to Perfluroalkylated γ-Spiroiminolactones - Tao, Lili; Fan, Zhenhua; Peng, Xin; Han, Jing; He, Weimin; Chen, Jie; Deng, Hongmei; Shao, Min; Zhang, Hui; Cao, Weiguo (Synthesis, 2018)
A variety of perfluoroalkyl-substituted γ-spiroiminolactones have been synthesized via a one-pot, three-component cascade reaction in which isocyanides, methyl perfluoroalk-2-ynoates and 1,2-diketones undergo highly regioselective Michael addition, nucleophilic addition and cyclization. This reaction has the advantages of good to excellent chemical yields, operationally simple procedure, and short reaction times.
Keywords: spiroiminolactones; perfluoroalkyl-substituted; isocyanide; multicomponent reaction; methyl perfluoroalk-2-ynoate